Welfare, the Earned Income Tax Credit, and the Labor Supply of Single Mothers - Meyer, B. D.; Rosenbaum, D. T. (Quarterly Journal of Economics, 2001)
During 1984–1996, welfare and tax policy were changed to encourage work by single mothers. The Earned Income Tax Credit was expanded, welfare benefits were cut, welfare time limits were added, and welfare cases were terminated. Medicaid for the working poor was expanded, as were training programs and child care. During this same time period there were unprecedented increases in the employment and hours of single mothers. We show that a large share of the increase in work by single mothers can be attributed to the EITC and other tax changes, with smaller shares for welfare benefit cuts, welfare waivers, training programs and child care programs.